Sexual maturity staging and affecting immune-hormonal factors in children aged 6-18 years living with HIV: experience from tertiary care center in North India - Ashwini Shivannavar; Alok Hemal; Hema Gupta Mittal (HIV & AIDS Review. International Journal of HIV-Related Problems)
Background Children living with human immunodeficiency virus (HIV) may experience growth failure and delay in sexual maturation. The aim of the study was to investigate sexual maturity rating and hormonal levels in children living with HIV aged 6-18 years.